Mitochondrial fission: firing up mitochondria in brown adipose tissue - Gao, Arwen W (Blackwell Publishing Ltd, 2014)
Brown adipose tissue (BAT) is an important site for energy expenditure, for instance to generate heat in times of cold exposure. BAT expansion and activation can increase energy dissipation of an organism. This involves the coordinated activation of mitochondrial metabolism and heat generation through uncoupling of oxidative phosphorylation. In this issue of The EMBO Journal, the Shirihai group uncovers a novel potentiation pathway for BAT energy expenditure. Changes in mitochondrial dynamics, in particular mitochondrial fission, act in synergy with fatty acid-induced uncoupling to activate BAT metabolism in response to the hormone norepinephrine.